Treasure Hunters - Smith, Jeff; Hamaker, Steve (New York, N. Y. Graphix / Scholastic, 2008)
The Bone cousins, Gran'ma Ben, and Thorn finally reach the city of Atheia, where they reunite with old friends and plan to thwart The Lord of the Locusts. The Pawan army has joined forces with Briar and the rat creatures, and danger increases as Thorn's visions get stronger. Meanwhile, Phoney Bone is convinced Atheia is a city rich in gold, and he is determined to find it!
Lucius -- The gate of Atheia -- The cold spot -- Pals -- To be or not to bee -- Moonwort -- The crown of horns.
430L
Keywords: Bone (Fictitious character); Treasure troves; Bone, Fone (Fictitious character); Bone, Phoney (Fictitious character); Bone, Smiley (Fictitious character); Graphic novels; Fantasy comic books, strips, etc